The impact of Enabling Collaborative Situations in AR-assisted consignment tasks - Compan, Nathan; Matias, Jérémy; Lutz, Matthieu; Rix-Lièvre, Géraldine; Brissaud, Daniel; Belletier, Clément; Coutarel, Fabien (Frontiers in Industrial Engineering, 2023)
The introduction of emerging technologies is often an opportunity to redesign the workstation. The ECS (Enabling Collaborative Situation) is a theoretical proposal that aims to deploy the operator's activity in a collaborative situation with an emerging technology. This criterion often seems to be neglected by designers. It is a practical tool for industrialists to guide the design of new work situations as well as for the evaluation of already existing situations. An experiment was designed to reproduce a consignment operation. The initial situation corresponded to a classic situation with a paper operating procedure. The second situation was assisted by an augmented reality (AR) device and corresponded to either a good intensity of ECS or a low intensity of ECS (which is classically observed in a factory). This study has succeeded in creating an ECS, and it is well perceived as such by the subjects, but the different improvements are not perceived as important enough to make the overall experience better (satisfaction, comprehension, accessibility, performance, etc.